2018
DOI: 10.1590/1678-4162-9560
|View full text |Cite
|
Sign up to set email alerts
|

Surgical sponge associated with platelets rich plasma in skin mesh grafts and layer in rabbits (Oryctolagus cuniculus)

Abstract: The aim of this study was to evaluate of the efficacy of PRP employment associated with surgical sponges to improve the integration of the graft in the recipient bed. It was held at the Veterinary Hospital UNESP, Campus of Jaboticabal - SP, a study of 64 rabbits, divided into eight groups with eight animals. The groups were divided in control with saline solution 0,9%, control with PRP both without the sponge, surgical sponge with PRP, surgical sponge without PRP, and were used mesh and layer grafts in the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although, visibly distinct, the macroscopic variables corresponding to the clinical evolution of the skin grafts were not quantified or statistically analyzed in this study. The subjectivity and high degree of observational interference in this type of analysis make microscopic evaluation more relevant, as demonstrated in other studies (STANLEY et al, 2013;PAZZINI et al, 2016;REIS FILHO et al, 2017). However, we believe it is relevant to report these observations here, because they are parameters found by lab assistants while changing the dressings of the skin grafts.…”
Section: Discussionmentioning
confidence: 80%
“…Although, visibly distinct, the macroscopic variables corresponding to the clinical evolution of the skin grafts were not quantified or statistically analyzed in this study. The subjectivity and high degree of observational interference in this type of analysis make microscopic evaluation more relevant, as demonstrated in other studies (STANLEY et al, 2013;PAZZINI et al, 2016;REIS FILHO et al, 2017). However, we believe it is relevant to report these observations here, because they are parameters found by lab assistants while changing the dressings of the skin grafts.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, although no significant difference existed, the results of the current study were consistent with those of Pazzini et al . 30 , who used PRP gel on cutaneous grafts associating surgical sponges as a compressive dressing and concluded that it favored healing and integration of the graft into the recipient bed without the presence of granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A cutaneous graft was subsequently obtained in the dorsal region of the thorax. A cutaneous incision measuring 1 cm 2 was formed, and measured 6 cm in the caudal direction to the spinal process of the first cervical vertebra. The depth limits were determined based on the anatomical references described in the literature 13 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation